2005
DOI: 10.1002/hec.999
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and costs of methadone treatment: results from a lifetime simulation model

Abstract: Several studies have examined the benefits and costs of drug treatment; however, they have typically focused on the benefits and costs of a single treatment episode. Although beneficial for certain analyses, the results are limited because they implicitly treat drug abuse as an acute problem that can be treated in one episode. We developed a Monte Carlo simulation model that incorporates the chronic nature of drug abuse. Our model represents the progression of individuals from the general population aged 18-60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 26 publications
1
73
0
Order By: Relevance
“…The latter study, although satisfying the quality criteria, appears to be a rather crude cost-benefit analysis with the data reported as cumulative drug costs, drug-free weeks and 'anticipated drug costs' for five different treatment modalities with insufficient detail about how some of these data are derived. In contrast, one of the most recent papers in our review, by Zarkin and colleagues, 150 used a transmission dynamic model, with a lifetime time horizon with respect to heroin use, treatment for heroin criminal behaviour, employment and healthcare use. The use of a dynamic model in this case is wholly appropriate when trying to estimate the population effect of transmission of HIV and other drug-related infectious diseases over time, but it is beyond the remit and the modelling deemed appropriate for use in the current report.…”
Section: Overview Of Findingsmentioning
confidence: 91%
See 1 more Smart Citation
“…The latter study, although satisfying the quality criteria, appears to be a rather crude cost-benefit analysis with the data reported as cumulative drug costs, drug-free weeks and 'anticipated drug costs' for five different treatment modalities with insufficient detail about how some of these data are derived. In contrast, one of the most recent papers in our review, by Zarkin and colleagues, 150 used a transmission dynamic model, with a lifetime time horizon with respect to heroin use, treatment for heroin criminal behaviour, employment and healthcare use. The use of a dynamic model in this case is wholly appropriate when trying to estimate the population effect of transmission of HIV and other drug-related infectious diseases over time, but it is beyond the remit and the modelling deemed appropriate for use in the current report.…”
Section: Overview Of Findingsmentioning
confidence: 91%
“…including direct and indirect costs associated with healthcare resource use, criminal activity and earnings), namely those of Dijkgraaf and colleagues 101 Goldschmidt, 149 Harris and colleagues, 144 Sirotnik and Bailey 142 and Zarkin and colleagues. 150 The remaining six studies took the perspective of a healthcare system: Barnett and colleagues 147,151 and Zaric and colleagues 145,146 reported results from the perspective of the US healthcare system, Sheerin and colleagues 148 took the perspective of the New Zealand health system and Doran and colleagues 143 took the perspective of the Australian Health Service.…”
Section: Perspectivementioning
confidence: 99%
“…There was no estimation of patients' time or employment outcomes, partly because of the high rates of unemployment among study participants. Zarkin et al (2005) included crime and employment impacts as well as health care costs and life years saved, in a model of the lifetime impacts of increased numbers treated and duration of treatment, in comparison to the status quo, using US data. Logan et al (2004) took a wider perspective in examining the question of whether US drug courts were cost-effective compared with no drug courts.…”
Section: Interventionsmentioning
confidence: 99%
“…A methodologically rigorous simulation study found that an additional $1 spent on increasing access to treatment yields $76 in discounted lifetime benefits. 8 Deregulation and increases in the number of physicians prescribing methadone have coincided with a 240% increase in the number of patients in treatment since 1996. Thus, economic incentives for community pharmacies to continue to dispense methadone must remain to ensure widespread access.…”
Section: Key Pointsmentioning
confidence: 99%